Karl-Erik Frandsen (red.): Kulturhistorisk Håndbog for Falster, 1986. Bd. 1: Sydfalster kommune. Bd. 2: Nykøbing Kommune. Bd. 3: Stubbekøbing Kommune. Bd. 4: Norre Alslev Kommune. - Korr Johansen, Erik (Historie/Jyske Samlinger, 1991)
Karl-Erik Frandsen (red.): Kulturhistorisk Håndbog for Falster, 1986. Bd. 1: Sydfalster kommune. Af Jens Ole Jensen. 323 s. Bd. 2: Nykøbing Kommune. Af Jens Ole Jensen. 282 s. Bd. 3: Stubbekøbing Kommune. Af Jens Ole Jensen og Karl-Erik Frandsen. 499 s. Bd. 4: Norre Alslev Kommune. Af Karl-Erik Frandsen. 547 s.